2004
DOI: 10.1002/eji.200324552
|View full text |Cite
|
Sign up to set email alerts
|

Induction of FOXP3‐expressing regulatory CD4pos T cells by human mature autologous dendritic cells

Abstract: Current literature suggests that T cells recognizing antigen on mature dendritic cells (DC) differentiate into effector T cells whereas tolerance is induced when antigen is presented by immature DC. We investigated the consequences of the interactions between immature or lipopolysaccharide-matured DC and CD4 pos T lymphocytes in absence of foreign antigen. While immature DC did not induce significant CD4 pos T cell activation, we observed that a significant fraction of CD4 pos T cells cultured with mature auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 48 publications
(46 reference statements)
7
100
1
1
Order By: Relevance
“…In addition, the release of IL-10 by CD11cϩ,CD11bϩ DCs from Peyer's patches of tolerized mice could play a role in inducing CD4ϩ, CD25ϩ T regulatory cells to differentiate. Several welldesigned studies have demonstrated that immature DCs, semi-immature DCs, fully mature DCs, or granulocytemacrophage colony-stimulating factor-pulsed DCs could cause naive T cells to differentiate into CD4ϩ,CD25ϩ T regulatory cells in the periphery (35)(36)(37)(38). However, the specialized subset of tolerogenic DCs generated under physiologic conditions, such as those seen in the nontransgenic autoimmune arthritis animal model, is yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the release of IL-10 by CD11cϩ,CD11bϩ DCs from Peyer's patches of tolerized mice could play a role in inducing CD4ϩ, CD25ϩ T regulatory cells to differentiate. Several welldesigned studies have demonstrated that immature DCs, semi-immature DCs, fully mature DCs, or granulocytemacrophage colony-stimulating factor-pulsed DCs could cause naive T cells to differentiate into CD4ϩ,CD25ϩ T regulatory cells in the periphery (35)(36)(37)(38). However, the specialized subset of tolerogenic DCs generated under physiologic conditions, such as those seen in the nontransgenic autoimmune arthritis animal model, is yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo vaccine setting, T cells stimulated by mockDCs could in any case exert an important regulatory influence on the vaccine response, as has been assumed with regard to AMLR in conventional inflammatory conditions. [22][23][24] The DC vaccine could also result in expansion of autoreactive T cells recognizing transfected antigens. Accordingly, patients should be monitored carefully with respect to potential autoimmune side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring Treg cells were traditionally described to be thymically-derived with the function of maintaining systemic homeostasis to control total lymphocyte numbers in order to protect the integrity of tissues and organs in vivo (Sakaguchi et al, 2001). More recently, Treg populations have been induced in vitro and in vivo via culturing with cytokines or in mouse models via pathogenic or allergenic stimulation (Verhasselt et al, 2004;Kretschmer et al, 2005;Luo et al, 2005;Skapenko et al, 2005;Moo-Young et al, 2006;Nicolson & Wraith, 2006;Strickland et al, 2006). The induced Treg populations also have the ability to control other lymphocytes in vivo however they differ from naturally occurring Treg in a number of ways which will be discussed below.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…In this context, an evolving role for RTDC may be to promote Treg cells capable of directly and actively suppressing the immune response to antigen once the antigen has been cleared (Jonuleit et al, 2001;Weiner, 2001;Martin et al, 2003;Verhasselt et al, 2004;Chen, 2006;Tarbell et al, 2006;Cools et al, 2007;Fujita et al, 2008). Akbari et al (2001) demonstrated that respiratory exposure to antigen (OVA) could induce phenotypically mature pulmonary DC that transiently produced IL-10.…”
Section: Role For Respiratory Tract Dendritic Cell In Regulatory T Cementioning
confidence: 99%